MENGUKUR DAMPAK ROA, ROE, DAN EPS TERHADAP HARGA SAHAM PERUSAHAAN TEKNOLOGI DI NASDAQ (2018-2023) - Akbar, Akbar Maulana Rivaldo (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2024)
This study aims to analyze the effect of Return on Assets (ROA), Earning per Share (ROE), and Earnings Per Share (EPS) on stock prices of companies listed on the Nasdaq for the period 2018-2023. The research method used is a quantitative study with a causal-comparative approach. The data utilized is secondary data obtained from the financial statements of companies accessed through the official Nasdaq website. The population in this study consists of technology subsector companies listed on Nasdaq, with a sample of ten companies selected using purposive sampling based on specific criteria. The independent variables in this study are Return on Assets (X1), Earning per Share (X2), and Earnings Per Share (X3), while the dependent variable is the stock price (Y). The research method applied is panel data regression using the EViews 13 application. The results of the study show that ROA and EPS have a positive and significant impact on stock prices, while ROE does not have a significant effect. These findings indicate that investors pay more attention to the profitability of companies as reflected by ROA and EPS in making investment decisions.